National accounts of the Netherlands 2015 - Netherlands. Centraal Bureau voor de Statistiek (The Hague: Statistics Netherlands, 2016)
The national accounts offer a systematic and consistent overview of the Dutch economy. These official overview statistics play a key role in economic and monetary policy-making and form the basis of the economic predictions and analyses of the Netherlands Bureau for Economic Policy Analysis. The national accounts are also crucial in determining payments to the European Union and in determining the extent to which the Netherlands meets the EMU norm. This book provides a concise overview of the most relevant macro-economic tables and indicators for the last six years.
Macroeconomics -- Supply, Use and input-output tables -- Final expenditure -- Production and generation of income -- Labour -- Sector accounts -- Other tables -- Explanations
Keywords: Netherlands; Finance; National income; National income--Accounting